2016
DOI: 10.1177/1756827716642159
|View full text |Cite
|
Sign up to set email alerts
|

Helical modes in combined Rayleigh–Taylor and Kelvin–Helmholtz instability of a cylindrical interface

Abstract: The effect of competing Rayleigh-Taylor and Kelvin-Helmholtz mechanisms of instability applied to a cylindrical two-fluid interface is discussed. A three-dimensional temporal linear stability model for the instability growth is developed based on the frozen time approximation. The fluids are assumed to be inviscid and incompressible. From the governing equations and the boundary conditions, a dispersion relation is derived and analyzed for instability. Four different regimes have been shown to be possible, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This also suggests the possibility of hybrid KH-RT instability where RT waves are modulated on the crest of KH waves (Zhao et al 2014;Mitkin & Theofanous 2017;Sharma et al 2021c) and appear as front-surface corrugations. It is worth noting that the 'hybrid KH-RT' mechanism referred to here is different from the 'combined KH-RT' mechanism studied by Vadivukkarasan & Panchagnula (2016 in which the KH and the RT instabilities occur simultaneously as equal contributors to the destabilization process. Whereas, in the hybrid KH-RT mechanism, the KH waves appear first, leading to an increase in the area of the air-liquid interface normal to the airflow direction, which provides a suitable platform for the subsequent occurrence of RT instability.…”
Section: Stage Ii: Rt Instability Asmentioning
confidence: 78%
“…This also suggests the possibility of hybrid KH-RT instability where RT waves are modulated on the crest of KH waves (Zhao et al 2014;Mitkin & Theofanous 2017;Sharma et al 2021c) and appear as front-surface corrugations. It is worth noting that the 'hybrid KH-RT' mechanism referred to here is different from the 'combined KH-RT' mechanism studied by Vadivukkarasan & Panchagnula (2016 in which the KH and the RT instabilities occur simultaneously as equal contributors to the destabilization process. Whereas, in the hybrid KH-RT mechanism, the KH waves appear first, leading to an increase in the area of the air-liquid interface normal to the airflow direction, which provides a suitable platform for the subsequent occurrence of RT instability.…”
Section: Stage Ii: Rt Instability Asmentioning
confidence: 78%
“…A complete understanding of the relation between the RTI and the KHI is important in understanding the hydrodynamic instability-driven mixing processes. In addition to the growth rate and final state, some studies have been made on the early linear and early nonlinear evolution of the coupled instability [39][40][41][42][43][44][45][46][47][48][49] . Both the instability modes and devolution processes that may be manifested when two such mechanisms occur simultaneously are of current interest.…”
Section: Introductionmentioning
confidence: 99%
“…Akula et al 43 showed that the superposition of shear on RTI at small Atwood number increases the mixing width and growth rate at early times. Vadivukkarasan et al [44][45][46] described the 3D destabilization characteristics of cylindrical and annular interfaces under the combined RTKHI, and the effects of various parameters on the most unstable wavenumbers were studied. Sarychev et al 47 found that an undulating topography on the interface coating/base material is resulted from the coupled RTKHI.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, the finite amplitude of waves on the jet surface as well as jet flapping may trigger the RT instability leading to the generation of droplets and ligaments. However, the possibility of combined action of both instabilities has been discussed by Vadivukkarasan and Panchagnula 25 who developed a three-dimensional temporal stability model for the growth of the instability and identified short wavelength helical mode when both KH and RT mechanisms are active on the cylindrical liquid jet. Recently, Matas and Cartellier 26 recognized the flapping instability as a mechanism leading to oscillation of the tail of the liquid jet near the breakup point.…”
Section: Introductionmentioning
confidence: 99%